Pengaruh Model Pembelajaran GENICS terhadap Metakognisi dan Strategic Thinking: (A Systematic Literature Review) - Devi Anggia Rizqi; Jodion Siburian; Raissa Mataniari (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The development of metacognitive skills and strategic thinking competency has become a central demand of 21st-century education. The GENICS learning model (Grouping, Exploring, Discussion, Individual Activity, Combining, Sharing) is considered to have strong potential in promoting active engagement and reflective learning processes. However, existing studies on GENICS are predominantly quantitative and tend to focus on general cognitive outcomes and meta-skills, while in-depth exploration of metacognitive and strategic thinking competencies—particularly through a mixed method embedded design—remains limited. This study aims to conduct a systematic literature review of research related to the GENICS model, metacognition, and strategic thinking to identify research trends, empirical findings, and existing gaps. The review employed identification, screening, and analytical stages of scientific articles indexed in Scopus and SINTA from 2019 to 2025. The findings indicate that: (1) GENICS has significant potential to facilitate students’ metacognitive regulation through collaborative and reflective activities; (2) explicit investigation linking GENICS to strategic thinking competency is still scarce; and (3) a mixed method embedded design is highly relevant for comprehensively examining both learning processes and outcomes. These findings highlight a substantial research gap and underscore the urgency of further mixed-method research in innovative instructional contexts.